Analysis of a Load Step Test at Ringhals 4 NPP using RELAP5 Code - Stathis, Athanasios (My University, 2015)
Ringhals 4 unit, a Westinghouse deign Pressurized Water Reactor, has recently undergone a pressurizer and steam generator replacement. In March 2015 the reactor was licenced to operate at the uprated 3300 MWth nominal thermal power level. Load Step Test is among the first tests performed in the reactor at the uprated power conditions. During the Load Step Test, while the reactor is in steady state, the turbine power is sharply reduced by 10 %. Fast insertion of the control rods follows and the reactor is stabilized in an intermediate steady state. After 3000 s in the intermediate steady state the control rods are quickly withdrawn in order to sharply increase the turbine power by 10 % and restore the reactor to its nominal steady state. The purpose of the Load Step Test is to verify that the control systems can mitigate the transient. The data from this test can be used for the assessment and improvement of RELAP5 model of Ringhals 4. Validation of the model was performed by the simulation of the transient. Thus, the first step is that the code reaches a realistic steady state close to the one of the plant in the beginning of the test. This task is accomplished. The challenges occurred during this stage are mentioned as well the way they were tackled. In addition, strategies for achieving steady state are touched upon. The next step is the simulation of the whole transient. The process/way of thinking that led to specific improvements in the model is described, as well as the key parameters for the further improvement of the model. In the end, the "goodness" of the improved model is assessed using the Fast Fourier Transformed Method (FFTBM). FFTBM proves that the model is capable of predicting the transient quite accurately.
Keywords: Energi; Kärnfysik; Energy; Nuclear physics